Survival of the mediated - Deuze Mark (Cultural Science)
Departing from a perspective of life as lived in rather than with media, this paper articulates the evolutionary context for people's near-complete immersion in media. Using examples such as the appropriation of the movie "Avatar" by activists around the world it is argued how our orientation to media provides adaptive advantage in contemporary postgeographical society.